PERANCANGAN USER INTERFACE PADA WEBSITE RSUD CIAMIS DENGAN METODE KANSEI ENGINEERING - Ilham Daulah; Rian Dwicahya Supriatman; Haisyam Maulana (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
The RSUD Ciamis website functions as a digital platform to deliver announcements, health services, and other health-related information to the public and patients. As an official information medium, this website plays an important role in maintaining communication between the hospital, patients, patients’ families, and other stakeholders. However, the current user interface design is considered less optimal in terms of usability, aesthetics, and emotional perspective. Such limitations may reduce user comfort, trust, and satisfaction. Therefore, a redesign of the interface is required, not only focusing on functionality but also considering users’ emotional perspectives and strengthening the brand identity of RSUD Ciamis. This study employed the Kansei Engineering method, which translates emotional impressions into concrete design elements. A total of 50 respondents were involved in evaluating five web interface specimens from Indonesian hospitals using ten selected Kansei words, namely firm, warm, simple, clear, modern, professional, calm, dynamic, clean, and safe. The research procedure consisted of several stages: investigation (selection of Kansei words, translation into semantic differential scales, determination of specimens, classification of design elements, and respondent selection), evaluation (data collection through questionnaires and statistical analysis), and recommendation (PLS analysis and design proposals). The study produced a user interface design for the RSUD Ciamis website that is expected to enhance visual appeal, clarity of information, and ease of navigation. Nevertheless, its effectiveness cannot be assured without post-implementation evaluation. Therefore, further research is recommended to conduct usability testing and explore additional Kansei words to enrich design insights and ensure continuous improvement.